Gender at Work at Home: Family Decisions, the Labour Market, and Girls' Contributions to the Family Economy - Bradbury, Bettina (Canadian Family History. Selected Readings, 1992)
Keywords: Enfants; Famille; Femmes; Travail

The Family Economy and Work in an Industrializing City: Montreal in the 1870s - Bradbury, Bettina (CHA / SHC, Historical Papers / Communications historiques, 1979)
Keywords: Enfants; Famille; Femmes; Saint-Jacques; Sainte-Anne; Travail

Women and Wage Labour in a Period of Transition: Montreal, 1861-1881 - Bradbury, Bettina (Histoire sociale / Social History, 1984)
Number: 33
Keywords: Famille; Femmes; Travail

The Family Economy and Work in an Industrializing City: Montreal in the 1870s - Bradbury, Bettina (Cities and Urbanization. Canadian Historical Perspectives, 1990)
Keywords: Enfants; Famille; Femmes; Saint-Jacques; Sainte-Anne; Travail

The Family Economy and Work in an Industrializing City: Montreal in the 1870s - Bradbury, Bettina (Interpreting Canada's Past. Vol. 2. After Confederation, 1986)
Keywords: Enfants; Famille; Femmes; Saint-Jacques; Sainte-Anne; Travail

The Family Economy and Work in an Industrializing City: Montreal in the 1870s - Bradbury, Bettina (The Social Development of Canada - Readings, 1983)
Keywords: Enfants; Famille; Femmes; Saint-Jacques; Sainte-Anne; Travail

Women and Wage Labour in a Period of Transition, 1861-1881 - Bradbury, Bettina (Canadian Labour History: Selected Readings, 1987)
Keywords: Famille; Femmes; Travail

The Family Economy and Work in an Industrializing City, Montreal in the 1870's - Bradbury, Bettina (Interpreting Canada's Past. Vol. 2: Post-Confederation, 1993)
Keywords: Enfants; Famille; Femmes; Saint-Jacques; Sainte-Anne; Travail

"Behind the Store": Montreal Shopkeeping Families between the Wars - Taschereau, Sylvie (Negotiating Identities in 19th- and 20th- Century Montreal, 2005)
Keywords: Alimentation; Famille; Magasins

Saving the Union's Jack: The Montreal Sailor's Institute and the Homeless Sailor, 1862-98 - Ingram, Darcy (Negotiating Identities in 19th- and 20th- Century Montreal, 2005)

L'économie familiale et le travail dans une ville en voie d'industrialisation: Montréal dans les années 1870 - Bradbury, Bettina (Maîtresses de maison, maîtresses d'école, 1983)
Keywords: Famille; Travail

Women and Wage Labour in a Period of Transition: Montreal, 1861-1881 - Bradbury, Bettina (Canadian Labour History: Selected Readings, 1994)
NOTICE DG
Keywords: Famille; Femmes; Travail